2005
DOI: 10.1038/sj.bjc.6602591
|View full text |Cite
|
Sign up to set email alerts
|

A prospective longitudinal study of performance status, an inflammation-based score (GPS) and survival in patients with inoperable non-small-cell lung cancer

Abstract: The value of an inflammation-based prognostic score (Glasgow Prognostic score, GPS) was compared with performance status (ECOG-ps) in a longitudinal study of patients (n ¼ 101) with inoperable non-small-cell lung cancer (NSCLC). At diagnosis, stratified for treatment, only the GPS (HR 2.32, 95% CI 1.52 -3.54, Po0.001) was a significant predictor of survival. In contrast, neither the GPS nor ECOG-ps measured at 3 -6 months follow-up were significant predictors of residual survival. This study confirms the progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 14 publications
4
133
0
2
Order By: Relevance
“…This work is consistent with previous work in patients with inoperable nonsmall-cell lung cancer (Forrest et al, 2003(Forrest et al, , 2004(Forrest et al, , 2005 and improves on the prediction of survival using an elevated C-reactive protein alone (Albuquerque et al, 1995;Zhang and Adachi, 1999). If these results are confirmed in larger studies, the GPS may be useful in the assessment of advanced breast cancer patients at diagnosis and the stratification of patients entering randomised trials.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This work is consistent with previous work in patients with inoperable nonsmall-cell lung cancer (Forrest et al, 2003(Forrest et al, , 2004(Forrest et al, , 2005 and improves on the prediction of survival using an elevated C-reactive protein alone (Albuquerque et al, 1995;Zhang and Adachi, 1999). If these results are confirmed in larger studies, the GPS may be useful in the assessment of advanced breast cancer patients at diagnosis and the stratification of patients entering randomised trials.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, we have shown that, using established cutoffs, a combination of an elevated C-reactive protein and hypoalbuminaemia, the Glasgow Prognostic score (GPS) has prognostic value, independent of stage and performance status, in patients with inoperable non-small-cell lung cancer (Forrest et al, 2003(Forrest et al, , 2004(Forrest et al, , 2005. However, there is no information on the prognostic value of this combination in patients with metastatic breast cancer.…”
mentioning
confidence: 99%
“…Serum albumin was previously demonstrated to predict poor long-term outcome following cancer resection independently of CRP and has subsequently been combined with CRP to produce prognostic inflammatory scores validated in varied maligancies. 23,31,32 The current study confirmed that serum albumin and cellular markers of the SIR may also exhibit independent prognostic significance in malignancy and, along with the CRS, the other independent predictor of outcome, could be combined to produce a novel score with high prognostic value. Of note, these data are all routinely available preoperatively.…”
Section: Discussionsupporting
confidence: 65%
“…2,13,20,23,26,31,39 For simplicity, high numbers of cells indicates cell numbers higher than the cut-off levels and low numbers of cells indicates cell numbers lower than the cut-off levels. Carstairs deprivation scores were analysed following allocation into established UK-based score quintiles.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation